An analysis for an ISO 11784/5 compliant mixed-signal ASIC, for animal RFID readers’ frontends [preprint] - Barbieri, Lucio (2025)
In this work a custom integrated circuit is presented, aimed at implementing a low-cost and high-performance RFID reader for the cattle industry. It was designed to be fully compliant with the ISO 11784/5 standard for animal ID @134.2kHz. Firstly, the reader-tag link was characterized and an adequate system topology was proposed. Then, an initial version of the analog RFID front-end was implemented using discrete electronic components, and tested. Using these measurement results, an AD conversion stage, and subsequent digital filters, were optimized in a second, mixed-signal version, of the RFID reader engine to be implemented in an ASIC. The complete reader circuit was designed in a 0.18 µm CMOS-HV technology including an analog front-end and programmable digital IIR filters, that can be adapted for both HDX and FDX ISO RFID tags. The resulting circuit occupies an area of less than 1.0mm².